2014
DOI: 10.1161/circresaha.115.303794
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Heterogeneity of Cardiac Fibroblasts Does Not Predict Pathological Proliferation and Activation

Abstract: Rationale: Fibrosis is mediated partly by extracellular matrix–depositing fibroblasts in the heart. Although these mesenchymal cells are reported to have multiple embryonic origins, the functional consequence of this heterogeneity is unknown. Objective: We sought to validate a panel of surface markers to prospectively identify cardiac fibroblasts. We elucidated the developmental origins of cardiac fibroblasts and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
312
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(341 citation statements)
references
References 38 publications
17
312
0
Order By: Relevance
“…Mechanical stress due to pressure overload activates the renin-angiotensin-aldosterone system (RAAS), triggering inflammatory signaling and leading to downstream stimulation of TGF-β cascades. Neurohumoral mediators, cytokines, and growth factors directly stimulate a fibrogenic program, triggering myofibroblast conversion and stimulating synthesis of large amounts of structural matrix proteins (103)(104)(105)(106). Stress-induced fibroblast activation in the pressure-overloaded myocardium may also be indirect, at least in part, requiring stimulation of fibrogenic cascades in cardiomyocytes and immune cells.…”
Section: Ecm In Cardiac Pressure and Volume Overloadmentioning
confidence: 99%
“…Mechanical stress due to pressure overload activates the renin-angiotensin-aldosterone system (RAAS), triggering inflammatory signaling and leading to downstream stimulation of TGF-β cascades. Neurohumoral mediators, cytokines, and growth factors directly stimulate a fibrogenic program, triggering myofibroblast conversion and stimulating synthesis of large amounts of structural matrix proteins (103)(104)(105)(106). Stress-induced fibroblast activation in the pressure-overloaded myocardium may also be indirect, at least in part, requiring stimulation of fibrogenic cascades in cardiomyocytes and immune cells.…”
Section: Ecm In Cardiac Pressure and Volume Overloadmentioning
confidence: 99%
“…It is generally thought that cardiac precursor cells represent multipotent lineage progenitors for cardiomyocytes, the endocardium and smooth muscle cells, a view that has been much influenced by studies of differentiating embryonic stem cells (ESCs) (summarized in Box 1). However, recent lineage-tracing studies have shown that although FHF and SHF cells arise from a common progenitor, probably in the pre-gastrulation embryo, their territories become geographically separate (Ali et al, 2014;Buckingham et al, 2005;Meilhac et al, 2004). FHF progenitors that form the primary heart tube and future left ventricle (Buckingham et al, 2005;Lescroart et al, 2014) are unipotent for cardiomyocytes or endothelial cell fates (Cohen-Gould and Mikawa, 1996;Lescroart et al, 2014).…”
Section: The Origin Of Cardiac Lineages In Developmentmentioning
confidence: 99%
“…An early CRE-based lineage-tracing experiment suggested that a subset of cardiac stromal fibroblasts arise de novo via endothelial-tomesenchymal transition (EndMT) from adult endothelial cells (Zeisberg et al, 2007). However, more recent lineage-tracing studies have shown that the proliferation and expansion of resident fibroblasts during cardiac hypertrophy accounts for almost all cardiac fibroblasts (Ali et al, 2014;Moore-Morris et al, 2014). Around 80% of the fibroblasts had their origins in the epicardium, with the remainder derived from the endocardium via EndMT (Ali et al, 2014;Moore-Morris et al, 2014), although a limited number of adult fibroblasts in the right atrium and outflow tract region might derive from neural crest cells (Ali et al, 2014).…”
Section: Origins and Plasticity Of Cardiac Fibroblastsmentioning
confidence: 99%
See 2 more Smart Citations